Identification of Physics Concepts in Tanjung Batu Knock Down House - Meitasari, Diana; Wiyono, Ketang (Kasuari: Physics Education Journal (KPEJ), 2024)
This research aims to identify the physics concepts present in various components of knock-down houses. Data collection was conducted through interviews, observations, and documentation. The research took place in the village of Tanjung Batu, Ogan Ilir Regency, South Sumatra. The method employed in this study was qualitative research with a descriptive explanatory form. The findings indicate that there are physics principles in several components of knock-down houses. These include the equilibrium of rigid bodies, evident in the stairs and supporting pillars of the house, the concept of torque that occurs when opening and closing windows, the concept of the center of gravity acting on the roof of the house, electrical concepts present in house lights, and the concepts of temperature and heat influenced by the house's materials. Additionally, the concept of measurement is evident in the lengths of the wooden beams used in the construction of the knock-down house. Based on the results of this research, it can be concluded that knock-down houses represent local wisdom that incorporates physics concepts suitable for educational purposes.